The Collective West Concept and Selected Western Actors (Germany, Norway, Estonia, NATO) in the Russian Media: Post-Crimea Dynamics (Global Journal of Human-Social Science, 1970)
The Post-Crimean period gave us a series of new concepts in international relations and one of them is the Collective West Concept Being invented in the academic sphere several years before the Crimean case the concept intervened the Russian public and political discourse In this article I argue that the Collective West concept has become an instrument of additional securitization of the West in the discourse of Russian media To prove the hypothesis I have used the discourse analysis and concept mining methodology I have created a sample of Media messages and by means of concept mining soft have coded the sample In this research project I was interested in finding correlations between the Collective West and separate Western countries and actors NATO Germany Norway Estonia After creating a correlation model for these concepts I have looked at the overall semantic and argumentation context of the concepts usage The results of the research give me an opportunity to conclude that the Collective West Concept is mostly used by Russian Media in negative context Such big international actors as Germany is included in the Collective West Concept when the context of speaking about it is also negative At the same time NATO is depicted as an instrument for the Collective West anti-Russian strategy Such small European countries as Norway and Estonia are not mentioned in correlation with the Collective West The main trend in Russian Media towards the West is simplification and intense securitization